Enabling environments for the exerciseof democracy in school - Cifuentes-Medina, José Eriberto (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper examines the relationship between democracy and its enabling environments in school. It also presents how educational agents established by law are governed –largely influenced by the interests of teachers, which are the educational agents for democracy– and their impact on society that is experienced from the school. It explores aspects of environments on democracy and its exercise in order to strength civic and citizenship skills of future citizens and to promote the construction of their duties and rights as students, to participate in school decisions, favoring development, promotion and defense of human rights.